Islamic Custom of Letter and Seal in Sarakata Manuscript “Surat-Surat dari Aceh” - Mustika Ayu Rakhadiyanti; Priscila Fitriasih Limbong (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2020)
This  paper  presents  a  study  on  Sarakata  manuscripts  from  the collection  of  the  National  Library  of  the  Republic  of  Indonesia.  The Sarakata analyzed in this research is  entitled "Surat-Surat dari Aceh" with  the  code  ML  447  written  in  the  19th  century  Jawi  script.  This Sarakata  consists  of  nine  letters,  four  of  which  are  analyzed  in  this study,  namely  Sarakata  3,  5,  6,  and  7.  These  Sarakatas  are  selected due  to  their  historical,  economic,  political,  social,  and  Islamic  law aspects.  The  text  structure  is  examined  using  'guidance  of correspondence'  in  Kitab  Tarasul.  It  is  found  that  compared  to Tarasul, SSA sarakata has five elements, one of which is not contained in  Kitab  Tarasul,  namely  the  pledge.  The  different  correspondence formats  are  due  to  the  fact  that  Aceh  has  its  Islamic  proprietary custom.  Another  segment  under  analysis  was  the  Sarakata  stamp (sikureueng  seal)  which  the  Aceh  sultans  used  in  establishing important  royal  letters.  This  seal  consists  of  one  or  nine  circles  with different  designs  and  decorations  depicting  each  king's  arts  and specific  objectives.  The  present  study  examines  this  usage  by employing  the  semiosis  process  by  Pierce.  The  study  results  indicate that  the  sikureueng  seal,  adorned  with  natural  and  geometric  shapes, represented  meanings  such  as  a  yearning  of  growth,  peace,  welfare, life, and longevity.